Factors affecting mammography screening behaviour among rural Vietnamese women. (26th August 2020) - Duong, Linh Thuy; Chen, Hui‐Mei; Liu, Chieh‐Yu; Chiou, Piao‐Yi
Abstract: Objectives: To identify factors associated with mammography screening behaviour and its predictors among rural Vietnamese women. Method: A predictive correlational study involving 120 women aged ≥ 40 years was conducted in the suburbs of Hanoi, Vietnam, in July 2018 by using Breast Cancer Awareness Measurement and the Champion Health Beliefs Model Scale. Mammography screening behaviour was assessed by asking participants about their previous mammography experience. Results: Only 16.7% of participants had undergone mammography screening. High education levels, high monthly family income, having family members or friends with breast cancer, and receiving physicians' recommendations increased the likelihood of participants screening for breast cancer. Mean scores on perceived susceptibility and perceived barriers differed significantly between participants who had and those who had not undergone screening ( t  = 4.31; p  < .001; t  = −5.05; p  < .001, respectively). Perceived susceptibility and perceived barriers significantly increased the predictive power of the hierarchical logistic model (critical value = 6.16; [ df  = 2]; p  = .046). Perceived barriers were the most significant predictors of screening behaviour (odds ratio 0.84; 95% CI, 0.71–0.99; p  = .039). Conclusion: Efforts are necessary to increase mammography awareness in the community and promote screening rates in Vietnam.